2022
DOI: 10.3857/roj.2021.00542
|View full text |Cite
|
Sign up to set email alerts
|

Limited field adaptive radiotherapy for glioblastoma: changes in target volume and organ at risk doses

Abstract: Objective: This study aimed to investigate the tumor volume changes occurring during limited-field radiotherapy (RT) for glioblastoma patients and whether a volume-adapted boost planning approach provided any benefit on tumor coverage and normal tissue sparing. Meterials and Methods: Twenty-four patients underwent simulation with magnetic resonance (MR) and computed tomography (CT) scans prior to RT (MR_initial, CT_initial) and boost treatment (MR_adapt, CT_adapt). For the boost phase, MR_initial and MR_adapt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 93 Indeed, several studies performed in patients that underwent adjuvant RT on conventional linacs demonstrated relevant changes of target volume between post-operative MRIs and planning MRIs 94 , 95 or MRIs performed at the first day of RT 96 98 and this could affect CTV definition. 94 Moreover, repeated MRIs performed during RT course invariably resulted in volumetric and/or geometric variations of disease and target volumes 98 102 and allowed to improve doses to the OARs 99 , 100 , 102 or to improve target coverage. 99 , 102 Volumetric variation of target volumes was heterogeneous, but in most series the majority of lesions progressively shrinked during radiotherapy 98 100 although expansion was consistently reported in a fraction of the cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 93 Indeed, several studies performed in patients that underwent adjuvant RT on conventional linacs demonstrated relevant changes of target volume between post-operative MRIs and planning MRIs 94 , 95 or MRIs performed at the first day of RT 96 98 and this could affect CTV definition. 94 Moreover, repeated MRIs performed during RT course invariably resulted in volumetric and/or geometric variations of disease and target volumes 98 102 and allowed to improve doses to the OARs 99 , 100 , 102 or to improve target coverage. 99 , 102 Volumetric variation of target volumes was heterogeneous, but in most series the majority of lesions progressively shrinked during radiotherapy 98 100 although expansion was consistently reported in a fraction of the cases.…”
Section: Resultsmentioning
confidence: 99%
“… 94 Moreover, repeated MRIs performed during RT course invariably resulted in volumetric and/or geometric variations of disease and target volumes 98 102 and allowed to improve doses to the OARs 99 , 100 , 102 or to improve target coverage. 99 , 102 Volumetric variation of target volumes was heterogeneous, but in most series the majority of lesions progressively shrinked during radiotherapy 98 100 although expansion was consistently reported in a fraction of the cases. 98 , 99 , 101 , 102 Adaptive radiotherapy based on serial MRI findings could improve doses to the OARs particularly in case of volume reduction 99 , 101 , 103 and guarantee adequate coverage in case of volumetric increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al observed better sparing of the OARs if IMRT was replanned with an MRI performed at the end of radiation treatment, mainly due to shrinkage of the resection cavity [31]. Şenkesen et al came to the same conclusions after MRI-based replanning of the boost volume [32]. The subsequent clinical impact and relevance (e.g., regarding treatment-related side effects, local control, and survival) are, however, still unclear.…”
Section: Discussionmentioning
confidence: 95%